Pengamatan Dampak Pengaruh Kelembahan Suhu Bagi Pelaku Usaha Tanaman Jamur - Diana Rusjayanti; Tion Sutiyono; Taufik Hidayat (Sultan Publsiher, 2024)
White oyster mushrooms are woody mushrooms that can be consumed and have high nutritional content including calcium, carbohydrates, iron, potassium and phosphorus. This time we are doing community service to mushroom plant business actors, aiming to find out the obstacles faced by business actors cultivating this mushroom plant, so that by analysing the impact of temperature on mushroom plants, we can contribute suggestions for white oyster mushroom plant business actors, so that crop yields increase. In observing this temperature, we used the method of interviewing business actors, then from the sources we interviewed, we made an analysis and we also made observations on mushroom plants. From the results of our observations we concluded that to get good mushroom production the temperature must be maintained around 24-28 Degrees Celsius, if the temperature is too high then the harvest will not be good. From the results of the observations made so that mushroom plant business actors can productively maintain the temperature in oyster mushroom plants so that the quality of the harvest is good.